2023
DOI: 10.4103/1673-5374.367838
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells, extracellular vesicles, and transcranial magnetic stimulation for ferroptosis after spinal cord injury

Abstract: Spinal cord injury is characterized by different aetiologies, complex pathogenesis, and diverse pathological changes. Current treatments are not ideal, and prognosis is generally poor. After spinal cord injury, neurons die due to various forms of cell death. Among them, ferroptosis causes dysfunction after spinal cord injury, and no existing traditional treatments have been indicated to block its occurrence. Meanwhile, emerging therapies using mesenchymal stem cells, extracellular vesicles, and transcranial ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…And in a related study, it was found that treatment with ferrostatin-1 significantly inhibited the onset of oxidative stress in brain tissue, improved the structure of brain tissue after hemorrhage, protected neurons, and promoted neurological function in recovery of rats. Another specific inhibitor, liproxstatin-1 (Lip-1), also significantly inhibited the elevated levels of ROS induced by mitochondrial lipid peroxidation and restored GPX4 expression levels, which in turn effectively reduced chronic compression injury of the rat ( Song et al, 2023 ). A recent study showed that CCI-induced mechanical and thermal nociceptive abnormalities in rats were significantly alleviated by intraperitoneal injection of Lip-1, while a decrease in iron content and a reduction in lipid peroxidation responses in spinal cord tissue were observed, along with a return to normal GPX4 expression levels.…”
Section: The Relationship Between Neuropathic Pain and Ferroptosismentioning
confidence: 99%
“…And in a related study, it was found that treatment with ferrostatin-1 significantly inhibited the onset of oxidative stress in brain tissue, improved the structure of brain tissue after hemorrhage, protected neurons, and promoted neurological function in recovery of rats. Another specific inhibitor, liproxstatin-1 (Lip-1), also significantly inhibited the elevated levels of ROS induced by mitochondrial lipid peroxidation and restored GPX4 expression levels, which in turn effectively reduced chronic compression injury of the rat ( Song et al, 2023 ). A recent study showed that CCI-induced mechanical and thermal nociceptive abnormalities in rats were significantly alleviated by intraperitoneal injection of Lip-1, while a decrease in iron content and a reduction in lipid peroxidation responses in spinal cord tissue were observed, along with a return to normal GPX4 expression levels.…”
Section: The Relationship Between Neuropathic Pain and Ferroptosismentioning
confidence: 99%